PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN - Noviyanti Kahar; Otto Randa Payangan; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine the influence of Customer Relationship Management consisting of human, process, to Customer Satisfaction and Loyalty. This research uses quantitative research approach. Quantitative research methods, used to examine the population or a particular sample, sampling techniques are generally done randomly, data collection using research instruments, quantitative / statistical data analysis with the aim to test the predefined hypothesis assisted with Smart PLS 2.0 program. The results showed that variable Customer Relationship Management consisting of human, process, and technology have a positive and significant influence on customer satisfaction. Customer Relationship Management consisting of human, process, and technology have positive and significant influence to customer loyalty, while satisfaction gives positive influence but not significant to customer loyalty. The indirect influence shows that satisfaction can mediate the influence of Customer Relationship Management consisting of human, process, and technology to customer loyalty.